Influence of manganese and nickel doping on optical and electric properties of CuO nanostructures for optoelectronic applications. (12th May 2022) - Bashir, Amna; Naz, Ambreen; Sultan, Muhammad; Bashir, Rabia; Ali, Naveed Zafar; Iqbal, Azhar; Akhter, Zareen
In recent years, metal oxide-based nanomaterials have gained considerable attention due to their wide range of applications in the field of catalysis, optoelectronics, and medicine. The current study is based upon the modification of optical and electronic properties of Cu(II) oxide (CuO) nanoparticles via doping. The CuO nanoparticles have been prepared by a simple hydrothermal route without using any template or surfactant. The optoelectronic modification of nanoparticles was done by the addition of dopants, i.e., 0%-5% nickel (Ni) and manganese (Mn). The powder X-rays diffraction (XRD) studies showed the improve crystallinitiy and increase particle size of CuO via doping. The field emission scanning electron microscopy (FE-SEM) showed the cauliflower and cluster-like nanostructures. The band-gap of Cu(II) oxide nanoparticles was investigated by the diffused reflectance spectroscopy (DRS). The photoluminescence (PL) measurements showed the increase in the surface defects and oxygen vacancies via the introduction of dopants. The presence of Ni and Mn in doped materials was confirmed by X-ray photoelectron spectroscopy (XPS). Hall measurements showed that the synthesised nanomaterials exhibit p-type conductivity. This modification of optoelectronic properties of CuO could present novel strategies leading to tailored metal oxide nanoparticles.